Real-Time PCR for Detection CP1 & CP5 Virulence Factors of Entamoeba Histolytica in Patients Stool Samples in Al - Najaf Al- Ashraf Province - Haiytham Mohamed Hamady; Zainab Ali Hussein (Kufa Journal for Nursing Sciences)
Objective: It aims to determine the genes characterization of CP1 and CP5 pathogenic factors of E.histolytica parasitic in stool samples of patients in AL- Najaf Al Ashraf Province